1990
DOI: 10.1093/jac/26.suppl_b.7
|View full text |Cite
|
Sign up to set email alerts
|

Usual and unusual antibacterial effects of quinolones

Abstract: Recently documented antibacterial effects of quinolones are reviewed. DNA gyrase is most likely to be the primary target site for these agents. Quinolones rapidly kill susceptible bacteria; the mechanisms of the bactericidal activity, still poorly understood, probably involve new protein synthesis. Quinolones alter membrane integrity before cell death, leading to leakage of cytoplasmic constituents. In Gram-negative bacteria, quinolones act as chelating agents for outer membrane divalent cations, disorganizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It has previously been reported that some marine bacteria have very long generation times (sometimes more than 1 week [6]) and are probably not detectable during a 24-h incubation period, suggesting that even the new DVC procedure underestimates the real fraction of viable cells within marine communities. Another hypothesis to explain the high differences between culturable and viable counts is the fact that quinolone antibiotics act as chelating agents on the divalent cations of the cellular wall (13), resulting in the passive entrance of nutrients into starved cells, which facilitates their recovery (27).…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been reported that some marine bacteria have very long generation times (sometimes more than 1 week [6]) and are probably not detectable during a 24-h incubation period, suggesting that even the new DVC procedure underestimates the real fraction of viable cells within marine communities. Another hypothesis to explain the high differences between culturable and viable counts is the fact that quinolone antibiotics act as chelating agents on the divalent cations of the cellular wall (13), resulting in the passive entrance of nutrients into starved cells, which facilitates their recovery (27).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of filamentation is probably related to the induction of the SOS response caused by initial DNA-gyrase inhibition and subsequent alterations in DNA topology and synthesis. The SOS pathway causes the block of cell division and, as a consequence, formation of filamentous forms [4,5,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the sequence of lethal events and the potential importance of secondary target sites require further investigation (2). [14CJpefloxacin labeling of Staphylococcus aureus membrane proteins showed binding of the quinolone to penicillin-binding protein (PBP) 2' and 0-lactamase (7), which are suggested to have a common ancestral gene (14).…”
mentioning
confidence: 99%